A bioenergetic framework for the temperature dependence of trophic interactions. (3rd June 2014) - Gilbert, Benjamin; Tunney, Tyler D.; McCann, Kevin S.; DeLong, John P.; Vasseur, David A.; Savage, Van; Shurin, Jonathan B.; Dell, Anthony I.; Barton, Brandon T.; Harley, Christopher D.G.; Kharouba, Heather M.; Kratina, Pavel; et al.
Abstract Changing temperature can substantially shift ecological communities by altering the strength and stability of trophic interactions. Because many ecological rates are constrained by temperature, new approaches are required to understand how simultaneous changes in multiple rates alter the relative performance of species and their trophic interactions. We develop an energetic approach to identify the relationship between biomass fluxes and standing biomass across trophic levels. Our approach links ecological rates and trophic dynamics to measure temperature‐dependent changes to the strength of trophic interactions and determine how these changes alter food web stability. It accomplishes this by using biomass as a common energetic currency and isolating three temperature‐dependent processes that are common to all consumer–resource interactions: biomass accumulation of the resource, resource consumption and consumer mortality. Using this framework, we clarify when and how temperature alters consumer to resource biomass ratios, equilibrium resilience, consumer variability, extinction risk and transient vs. equilibrium dynamics. Finally, we characterise key asymmetries in species responses to temperature that produce these distinct dynamic behaviours and identify when they are likely to emerge. Overall, our framework provides a mechanistic and more unified understanding of the temperature dependence of trophic dynamics in terms of ecological rates, biomass ratios and stability.